Scientific Substantiation of the Creation and Prospects for the Development of an Epidemiological Surveillance System for Infection Caused by the Epstein-Barr Virus - T. V. Solomay; E. G. Simonova; T. A. Semenenko (Эпидемиология и вакцинопрофилактика, 2022)
Relevance. At the present stage, the Russian Federation does not have a coherent system of supervision and control of infection caused by the Epstein-Barr virus (EBV), while there is an epidemiological problem with this pathology, requiring the development and adoption of a set of adequate management decisions. The goal is to scientifically substantiate the creation of an epidemiological surveillance system (ES) for EBV -infection in Russia. Materials and methods. Based on the results of previous studies, an assessment of the manifestations of the epidemic process of EBV infection and measures aimed at each of its links was carried out. Results. The structure and content of the system of epidemiological surveillance of EBV infection are presented. Conclusion. To implement and improve the effectiveness of EBV-infection control, it is necessary to adjust existing and develop new regulatory and methodological documents that allow introducing: a standard definition of the case of EBV-infection and new approaches to accounting and registration; studies of nasopharyngeal smear material for the presence of EBV genetic material as part of the monitoring of influenza and ARVI pathogens; algorithms for the examination of patients with diagnoses that do not exclude the presence of active EBV-infection, as well as organ, tissue and cell donors with the determination of a complex of nonspecific immunological markers (neopterin, melatonin, C-reactive protein, ALT); standard operating procedures for medical professionals for the identification and isolation of patients with active EBV-infection, clinical and laboratory diagnostics, registration and accounting, the use of personal protective equipment and nonspecific immunoprophylaxis. Also, improving the control of EBVinfection is impossible without continuing scientific research; professional training of medical workers on the clinic, diagnosis, epidemiology and prevention of EBV-infection; development of modern visual methods and means of informing the population about the clinic and prevention of EBV-infection.